Praktik Penggunaan Merek Dagang pada Warung Cabang Purnama di desa Cukir Perspektif Etika Bisnis Islam - Umam, Nasrul; Asi Islami, Trinah (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2024)
This research discusses the use of Trademarks on a product that is traded. The use of the trademark is discussed in terms of the perspective of Islamic business ethics, so as to know how Islamic law regulates the norms that must be applied in trade. Business ethics is an action taken or carried out by business actors in running their business, one of which is by providing protection and being responsible for the products issued, the trademark becomes one of the efforts in this regard. As one example that is used as the object of research this time is the Bebek Goreng Purnama Branch shop located in Cukir village. This research aims to explain the practice of using brands in the business, as well as how the perspective of Islamic business ethics on its application. This type of research uses juridical-empirical. This research uses a phenominological approach and conceptual approach. The results of the study concluded that the Purnama branch of the duck stall uses a trademark that has not fulfilled the license or does not have legality. Based on the perspective of Islamic Business Ethics, Purnama branch duck stall in Cukir Village, Diwek District, Jombang Regency has not fully implemented Islamic business ethics, such as the principles of unity, balance, freedom of will, responsibility and truth. Keywords: trademark, Islamic business ethics, full branch duck shop